Mirror, mirror on the wall: hypercalcemia as a consequence of modern cosmetic treatment with liquid silicone - Schanz, Jurik; Flux, Katharina; Kircher, Claudia; Tsioga, Maria; Hartschuh, Wolfgang; Nawroth, Peter Paul; Rudofsky, Gottfried (Medical science monitor, 2012)
BACKGROUND: Hypercalcemia is a common problem in clinical practice and can be related to endocrine disorders or malignant disease, especially in elderly patients. Although rare, other causes can also be responsible. CASE REPORT: Granulomatous inflammation of the skin and lymph nodes induced by intravenous or injectable silicone is a rare condition of hypercalcemia that is usually not within the scope of differential diagnosis. Here, we report a 72-year-old woman with symptomatic hypercalcemia related to cosmetic treatment of the neck. Topical applied liquid silicone by means of a focal ultrasound device induced extensive granulomatous inflammation of the skin and local lymph nodes, being the underlying cause for hypercalcemia in this case. CONCLUSIONS: In rare cases, symptomatic hypercalcemia can be caused by silicone due to a severe granulomatous tissue reaction. This is the first time that a transdermal silicone treatment has been reported to cause severe granulomatous tissue inflammation.